Socioeconomic heterogeneity in the effect of health shocks on earnings: Evidence from population-wide data on Swedish workers - Petter Lundborg; Martin Nilsson; Johan Vikström (Institute for the Study of Labor (IZA), 2011)
In this paper, we estimate socioeconomic heterogeneity in the effect of unexpected health shocks on labor market outcomes, using register-based data on the entire population of Swedish workers. We effectively exploit a Difference-in-Difference-in-Differences design, in which we compare the change in labor earnings across treated and control groups with high and low education levels. If the anticipation effects are similar for individuals with high and low education, any difference in the estimates across socioeconomic groups could plausibly be given a causal interpretation. Our results suggest a large amount of heterogeneity in the effects, in which individuals with a low education level suffer relatively more from a given health shock. These results hold across a wide range of different types of health shocks and become more pronounced with age. Our results suggest that socioeconomic heterogeneity in the effect of health shocks offers one explanation for how the socioeconomic gradient in health arises.
urn:nbn:de:101:1-201111303534
Keywords: I10; I12; I14; 330; health; health shocks; socioeconomic status; life-cycle; Gesundheit; Sozialer Status; Lebensverlauf; Schweden